ANALISIS KEBUTUHAN KAMUS DIGITAL BIPA BERBASIS MUATAN BUDAYA LOKAL UNTUK MAHASISWA ASING - Luthfa Nugraheni; Rani Setiawaty (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aimed to describe the characteristics of legends originating from Central Java and analyse the need for a BIPA digital dictionary based on local content for international students. This research used a mixed-methods approach with a sequential exploratory design. Qualitative data were obtained through observation, interviews, and documentation, while quantitative data were gathered through questionnaires completed by 12 international students and one BIPA instructor in Central Java. Qualitative data were analysed using the interactive model, while quantitative data were analysed by calculating the mean score. The results of the study show that the legends most favoured by international students are local and personal legends, whereas religious legends are less favoured, and supernatural legends were not found. Moreover, the majority of respondents expressed a preference for illustrated and descriptive digital dictionaries. The theoretical implication of this research is the enrichment of BIPA studies through the integration of local culture in the development of digital dictionaries. Practically, the findings offer guidance for instructors and media developers in designing digital dictionaries based on local content.